Endoscopic ultrasound-guided biopsy in chronic liver disease: a randomized comparison of 19-G FNA and 22-G FNB needles - Mok, Shaffer R. S.; Diehl, David L.; Johal, Amitpal S.; Khara, Harshit S.; Confer, Bradley D.; Mudireddy, Prashant R.; Kovach, Alicia H.; Diehl, Mia M.; Kirchner, H. Lester; Chen, Zong-Ming E. (Endoscopy International Open, 2019)
Background and study aims Endoscopic ultrasound-guided liver biopsy uses a 19-gauge (G) needle for parenchymal liver biopsies. We evaluated tissue yields with a 22G fine-needle biopsy (FNB) versus 19G FNA fine-needle aspirate (FNA) device. Patients and methods Biopsies were obtained from 20 patients using the 19G FNA and 22G FNB randomizing each in a cross-over fashion with a blinded outcome assessor. Tissue adequacy for histologic evaluation was the primary outcome, or the proportion of specimens obtaining pathologic diagnosis (portal structures ≥ 5 or length of the longest piece ≥ 15 mm). Additional secondary outcomes included portal and centrilobular inflammation/fibrosis, length of the longest piece, aggregate specimen length, and small (< 5 mm), medium (5 – 8 mm) and large (> 8 mm) fragments. Results were compared in a per needle basis. Patients with cirrhosis were excluded.Results Eighty biopsies (40 each 19G FNA and 22G FNB) were obtained. Tissue adequacy was greater for the 19G FNA (88 %) versus 22G FNB (68 %), (P = 0.03). There was no difference in total portal structures for the 19G FNA (7.4) and 22G FNB (6.1), (P = 0.28). There was no difference in pre-processing outcomes. After processing, length of the longest piece was higher for the 19G FNA (9.1 mm) versus 22G FNB (6.6 mm), (P = 0.02). More total post-processing small fragments 29.9 versus 20.7, (P = 0.01) and fewer large fragments 1.0 versus 0.4 for the 22G FNB (P = 0.01) were detected. Conclusions Tissue adequacy was higher for the 19G FNA versus 22G FNB needle. The 22G FNB needle produced samples more prone to fragmentation during specimen processing.